2022
DOI: 10.1111/jocn.16232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision: A mechanism to support person‐centred practice? An integrative review of the literature

Abstract: Aims To explore whether clinical supervision has an influence on person‐centred practice. Background The ability to deliver person‐centred care and the ability to engage in reflective practice are two key skills expected of nurses. Person‐centred care shifts nurses thinking from the patient's disease state to their personhood. Clinical supervision has been proposed as a place to explore person‐centred care. Person‐centred practice extends person‐centredness to enhance healthful relationships between care provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Reflection is an established approach to learning (Campbell & Rogers, 2022; Moon, 2004; Schon, 1991) and the development of individual practice across a range of sectors (Kraft et al, 2021). Reflection with a mentor or supervisor is a well‐established mechanism for personal development and support within health and care services but is relatively unexplored in the context of delivery and embedding of person‐centred dementia care (Edgar et al2023). This study adds to this body of knowledge by demonstrating observation and reflection are seen as feasible mechanisms to facilitate the delivery of PCC.…”
Section: Discussionmentioning
confidence: 99%
“…Reflection is an established approach to learning (Campbell & Rogers, 2022; Moon, 2004; Schon, 1991) and the development of individual practice across a range of sectors (Kraft et al, 2021). Reflection with a mentor or supervisor is a well‐established mechanism for personal development and support within health and care services but is relatively unexplored in the context of delivery and embedding of person‐centred dementia care (Edgar et al2023). This study adds to this body of knowledge by demonstrating observation and reflection are seen as feasible mechanisms to facilitate the delivery of PCC.…”
Section: Discussionmentioning
confidence: 99%
“…Chenoweth et al (2015) also reported that staff understanding, knowledge, acceptance and perseverance in applying person-centred principles were crucial factors for improving PCC, which resonates with the findings in the current study. However, a recent review reported that clinical supervision has the potential to increase self-awareness and enable staff to reflect upon themselves and become aware of the choices they make in practice, which in turn has the potential to make staff choose future behaviours consistent with their new insights (Denise et al, 2022). Seen in relation to the current study, an important implication for management and stakeholders that strive to promote person-centred practices may be that offering clinical supervision to address negative mindsets and low motivation will allow staff to reflect on their choices and behaviours and the subsequent risk of lower quality care.…”
Section: Discussionmentioning
confidence: 99%
“…leadership, new graduates, nurse-patient relationships, organisational behaviour, personcentred, practice development, practice-based learning, professional development, quantitative approaches, reflective practice A number of recent position papers advocate that all nurses and midwives entering a workforce should have access to clinical supervision that meets individual needs (Australian College of Midwives et al, 2019;Key et al, 2019). Clinical supervision is a broad term, not universally defined or applied (Edgar et al, 2022). Bond and Holland (2010) define it as 'the regular protected time for facilitated in-depth reflection, on complex issues influencing clinical practice' (Bond & Holland, 2010, p. 10).…”
Section: Contribution To Wider Communitymentioning
confidence: 99%
“…There is support that clinical supervision could enhance person‐centred care (Bond & Holland, 2010). A recent literature review combining the two concepts of person‐centred practice and clinical supervision found clinical supervision could provide a space to discuss the meaning of person‐centred care and consider the barriers to its practice however there is lack of evidence that it enhances person‐centredness as a stand‐alone strategy in nursing (Edgar et al., 2022). The review also highlighted the importance of a supportive supervisor and their person‐centred attributes.…”
Section: Introductionmentioning
confidence: 99%